Abstracts for ESCCA 2014 Conference: Exploring New Frontiers in Flow Cytometry September 14–17, 2014, Lisbon, Portugal. Issue 6 (November 2014) - Unknown
<x xml:space="preserve">Abstract</x> We are pleased to present abstracts from ESCCA 2014: Exploring New Frontiers in Flow Cytometry. The meeting, a joint production of the European Society for Clinical Cell Analysis (ESCCA) and the Iberian Society for Cytometry (SIC), has been of major importance for education and scientific exchange in basic, translational and clinical applications in cytometry; in particular flow cytometric applications in Hematology, Immunology, Cancer and Cell Biology. The meeting took place in Lisbon, Portugal on September 14–17, 2014, and was chaired by Dr. Maria Arroz (Lisbon, Portugal). The abstracts are available as Online Supporting Information.